Physical activity‐induced alterations of the gut microbiota are BMI dependent. Issue 4 (21st March 2023) - Shah, Shrushti; Mu, Chunlong; Moossavi, Shirin; Shen‐Tu, Grace; Schlicht, Kristina; Rohmann, Nathalie; Geisler, Corinna; Laudes, Matthias; Franke, Andre; Züllig, Thomas; Köfeler, Harald; Shearer, Jane
Abstract: Physical inactivity is one of the leading causes of chronic metabolic disease including obesity. Increasing physical activity (PA) has been shown to improve cardiometabolic and musculoskeletal health and to be associated with a distinct gut microbiota composition in trained athletes. However, the impact of PA on the gut microbiota is inconclusive for individuals performing PA in their day‐to‐day life. This study examined the role of PA and hand‐grip strength on gut microbiome composition in middle‐aged adults (40–65 years, n  = 350) with normal (18.5–24.9 kg/m 2 ) and overweight (25–29.9 kg/m 2 ) body mass index (BMI). PA was recorded using the International Physical Activity Questionnaire, and hand‐grip strength was measured using a dynamometer. Serum samples were assessed for lipidomics while DNA was extracted from fecal samples for microbiome analysis. Overweight participants showed a higher concentration of triacylglycerols, and lower concentrations of cholesteryl esters, sphingomyelin, and lyso‐phosphotidylcholine lipids ( p  < .05) compared with those with normal BMI. Additionally, overweight participants had a lower abundance of the Oscillibacter genus ( p  < .05). The impact of PA duration on the gut microbiome was BMI dependent. In normal but not overweight participants, high PA duration showed greater relative abundance of commensal taxa such as Actinobacteria and Proteobacteria phyla, as well as Collinsella and Prevotella genera ( p  < .05). Furthermore, in males with normal BMI, a stronger grip strength was associated with a higher relative abundance of Faecalibacterium and F. prausnitzii ( p  < .05) compared with lower grip strength. Taken together, data suggest that BMI plays a significant role in modeling PA‐induced changes in gut microbiota. Abstract : Physical activity is a potent mediator of gut microbiota composition. In this study, the impact of low, moderate, and high physical activity levels on gut microbiome composition was examined in middle‐aged adults with normal and overweight body mass index (BMI). Data were collected using online surveys, anthropometric measurements, 16S rRNA microbial sequencing, and serum lipidomics. Findings show the importance of BMI in attaining physical activity‐induced gut microbiome changes.